Psychometric properties of the standardized assessment of concussion in youth football: Validity, reliability, and demographic factors. Issue 4 (2nd October 2021) - Maerlender, Arthur; Smith, Eric; Brolinson, P. Gunnar; Urban, Jillian; Rowson, Steven; Ajamil, Amaris; Campolettano, Eamon T.; Gellner, Ryan A.; Bellamkonda, Srinidhi; Kelley, Mireille E.; Jones, Derek; Powers, Alex; et al.
Abstract: The objective of this study was to determine the psychometrics (reliability, validity) of the original Standardized Assessment of Concussion (SAC) in a youth sample (ages 11 to 13). Demographic factors of race, level of vocabulary knowledge, mother's level of education were also considered. Over 150 youth football athletes completed the SAC and a brief battery of NIH Toolbox cognitive tests as part of a larger study on biomechanical factors in youth sport concussion. This was a within-subjects design (pre-season, post-season assessments), and correlational analysis of convergent and discriminant validity. Between groups analysis based on demographic differences was also employed. The pre-season SAC scores were not different by age; however, SAC scores were statistically different by race: t( 155) = 3.162, p  = .002, d  = .519. Maternal level of education and participant vocabulary scores were related to racial group membership. Convergent and discriminant validity were established compared to NIH Toolbox tests of memory and speed. Pre–post-season tests for 108 participants established marginally acceptable test–retest reliability (ICC = .692). These data support the use of the original SAC in youth football although clinicians must be aware of racial differences in scores.